1993
DOI: 10.1128/mcb.13.3.1363
|View full text |Cite
|
Sign up to set email alerts
|

V(D)J recombination: signal and coding joint resolution are uncoupled and depend on parallel synapsis of the sites.

Abstract: V(D)J recombination in lymphoid cells is a site-specific process in which the activity of the recombinase enzyme is targeted to signal sequences flanking the coding elements of antigen receptor genes. The order of the steps in this reaction and their mechanistic interdependence are important to the understanding of how the reaction fails and thereby contributes to genomic instability in lymphoid cells. The products of the normal reaction are recombinant joints linking the coding sequences of the receptor genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 39 publications
4
37
2
Order By: Relevance
“…Bead release activity can be ablated by decreasing inter-RSS separation from 137 to 73 bp (Fig. S7 D and E), which would be predicted to interfere with RSS synapsis (28) and has been shown to reduce cleavage in biochemical assays (29). Notably, the block to bead release imposed by the 73-bp intersignal distance is overcome when Mn 2+ is used in place of Mg 2+ in the reaction buffer (Fig.…”
Section: Dynamics Of 12/23 Rule-regulated Bead Release As a Function Ofmentioning
confidence: 99%
“…Bead release activity can be ablated by decreasing inter-RSS separation from 137 to 73 bp (Fig. S7 D and E), which would be predicted to interfere with RSS synapsis (28) and has been shown to reduce cleavage in biochemical assays (29). Notably, the block to bead release imposed by the 73-bp intersignal distance is overcome when Mn 2+ is used in place of Mg 2+ in the reaction buffer (Fig.…”
Section: Dynamics Of 12/23 Rule-regulated Bead Release As a Function Ofmentioning
confidence: 99%
“…Several lines of evidence provide additional support for a synapsis model. Previous experiments demonstrated that shortening the distance between the RSS to less than 100 bp, which would physically hinder synapsis, also inhibits product formation (Lewis & Hesse 1991;Sheehan & Lieber 1993;Akamatsu et al 1994). Similar results have recently been obtained in a cell-free system (Eastman et al 1996).…”
Section: A Synapsis Model For V(d)j Recombinationmentioning
confidence: 99%
“…Analysis of artificial recombination substrates in cultured cells has shown that recombination is severely inhibited when the distance between the RSS is decreased to less than 100 nucleotides, a distance which should inhibit synapsis (Lewis & Hesse 1991;Sheehan & Lieber 1993;Akamatsu et al 1994). Further evidence supporting a requirement for synapsis is provided by certain V(D)J-related events which, in principle, would require cleavage at only a single RSS.…”
Section: Introductionmentioning
confidence: 99%
“…Third, the efficiency of signal joint completion appears to be less than 100% (5,6). And fourth, coding joints appear to form under conditions where signal joints are unlikely to form efficiently (23,33 There is some feature of the sonicated salmon sperm DNA that may affect V(D)J recombination or the transfection procedure (Tables 1 and 2). At this point, it is difficult to know how the carrier DNA is adversely affecting precision at the signal joint.…”
Section: Discussionmentioning
confidence: 99%
“…Four of these are representatives of each of the four double-strand break repair complementation groups that have been identified in Chinese hamster cells (8,14,38,40). The remaining two lines are X ray sensitive but not double-strand break repair deficient (15,39 (11,23,33). These substrates all undergo V(D)J recombination in hamster fibroblasts.…”
mentioning
confidence: 99%